Study of the Principle of Ad-darurah Tubih Al-mahzurat in Islamic Criminal Law: The Case of Euthanasia - Mulyono Jamal; Habiburrahman Mustofa (al-Afkar, Journal For Islamic Studies, 2026)
Euthanasia is a global issue that continues to be debated, especially from a legal and ethical perspective. In Islamic law, the principle of protection of life (hifz al-nafs) is the main basis for rejecting the practice of euthanasia. However, there is a fiqh principle Ad-darurah tubih al-mahzurat which permits prohibited actions in emergency situations, thus giving rise to debate whether this principle can be applied to euthanasia. This study aims to examine the application of this principle in the context of euthanasia based on Islamic law and compare it with positive legal regulations in various countries. The research method used is a qualitative study with a normative approach, involving literature analysis from classical books, fatwas of scholars, Islamic legal journals, and positive legal regulations. The results show that Islamic law generally rejects euthanasia because it is considered contrary to the principles of maqasid sharia. Although there are fatwas that permit certain medical procedures in emergency situations, euthanasia remains categorized as an act that is not permitted by Islamic criminal law. In contrast, several Western countries have legalized euthanasia with strict regulations, unlike Muslim countries, which generally prohibit the practice. The conclusion of this study confirms that the application of emergency rules in euthanasia must consider the principles of maqasid sharia as well as broader ethical and legal aspects. Therefore, further study and coordination between Islamic scholars, medical professionals, and policymakers are needed to formulate regulations that align with Islamic principles and developments in modern medicine.